2018
DOI: 10.1097/prs.0000000000004992
|View full text |Cite
|
Sign up to set email alerts
|

Fat Graft Safety after Oncologic Surgery: Addressing the Contradiction between In Vitro and Clinical Studies

Abstract: Background: The authors investigate the in vitro and in vivo interaction of human breast cancer cells and human adipose-derived stem cells to address the controversy on the safety of postmastectomy fat grafting. Methods: The authors co-cultured human adipose-derived stem cells and MDA-MB-231 breast cancer cells in an in vitro cell migration assay to examine the migration of breast cancer cells. In the in vivo arm, the authors injected breast cancer cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…A separate study showed that free fatty acids released by subcutaneous fat inhibit the proliferation of MCF-7 as a possible mechanism [29]. In line with our in vitro results showing no changes in MDA-MB-231 cells' proliferation pattern in co-culture, fat grafting studies in mice showed no significant changes in the MDA-MB-231 tumor volume [22,25]. On the other hand, two independent studies using a transwell paracrine co-culture system showed an increase in the MCF-7 cells' proliferation upon incubation with lipoaspirate [20,21].…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…A separate study showed that free fatty acids released by subcutaneous fat inhibit the proliferation of MCF-7 as a possible mechanism [29]. In line with our in vitro results showing no changes in MDA-MB-231 cells' proliferation pattern in co-culture, fat grafting studies in mice showed no significant changes in the MDA-MB-231 tumor volume [22,25]. On the other hand, two independent studies using a transwell paracrine co-culture system showed an increase in the MCF-7 cells' proliferation upon incubation with lipoaspirate [20,21].…”
Section: Discussionsupporting
confidence: 83%
“…Despite the large number of studies surrounding the topic, the field still lacks a clear direction due to conflicting reports from the variable choices of in vitro and in vivo study models. For example, in vitro studies utilized ASCs, in vitro differentiated adipocytes or floating adipocytes as the co-culture interaction partner of breast cancer cells, and reported the tumorigenic behavior of the breast cancer cells [14,16,20,22]. These interactive studies may not reflect the actual clinical scenario of AFT, where lipoaspirates are injected into tumor beds that may or may not have remnant active tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations